Anti-Lipolysis Induced by Insulin in Diverse Pathophysiologic Conditions of Adipose Tissue - Zhao J (Dove Medical Press, 2020)
Jia Zhao,1 YaYun Wu,1 XiangLu Rong,1– 3 CuiWen Zheng,1 Jiao Guo1– 3 1Guangdong Metabolic Diseases Research Center of Integrated Chinese and Western Medicine, Guangdong Pharmaceutical University, Guangdong, People’s Republic of China; 2Guangdong TCM Key Laboratory for the Prevention and Treatment of Metabolic Diseases, Guangdong, People’s Republic of China; 3Joint Laboratory of Guangdong Province and Hong Kong and Macao Regions on Metabolic Diseases, Guangdong, People’s Republic of ChinaCorrespondence: Jiao GuoGuangdong Metabolic Disease Research Center of Integrated Chinese and Western Medicine, Guangdong Pharmaceutical University, 280 Waihuan East Road, Guangzhou University City, Panyu District, Guangzhou, Guangdong Province 510006, People’s Republic of ChinaTel +86 20 39352818Email gyguoyz@163.comAbstract: As an important energy reservoir, adipose tissue maintains lipid balance and regulates energy metabolism. When the body requires energy, adipocytes provide fatty acids to peripheral tissues through lipolysis. Insulin plays an important role in regulating normal fatty acid levels by inhibiting lipolysis. When the morphology of adipose tissue is abnormal, its microenvironment changes and the lipid metabolic balance is disrupted, which seriously impairs insulin sensitivity. As the most sensitive organ to respond to insulin, lipolysis levels in adipose tissue are affected by impaired insulin function, which results in serious metabolic diseases. However, the specific underlying mechanisms of this process have not yet been fully elucidated, and further study is required. The purpose of this review is to discuss the effects of adipose tissue on the anti-lipolysis process triggered by insulin under different conditions. In particular, the functional changes of this process respond to inconsonantly morphological changes of adipose tissue.Keywords: adipose tissue, insulin, anti-lipolysis